Sodium houttuyfonate effectively treats acute pulmonary infection of Pseudomonas aeruginosa by affecting immunity and intestinal flora in mice - Zhuang, Tian; Hu, Mengxue; Wang, Jian; Mei, Longfei; Zhu, Xiaoxiao; Zhang, Haitao; Jin, Feng; Shao, Jing; Wang, Tianming; Wang, Changzhong; Niu, Xiaojia; Wu, Daqiang (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Pseudomonas aeruginosa is a major nosocomial pathogen that frequently causes ventilator-associated pneumonia in specific populations. Sodium houttuyfonate (SH) has shown mild antibacterial activity against P. aeruginosa in vitro, but the mechanism of potent antimicrobial activity of SH against P. aeruginosa infection in vivo remains unclear. Methods Here, using the mouse pneumonia model induced by P. aeruginosa nasal drip to explore the therapeutic effects of SH. Results We found that SH exhibits dose-dependent therapeutic effects of reducing P. aeruginosa burden and systemic inflammation in pneumonia mice. SH ameliorates inflammatory gene expression and production of inflammatory proteins, such as interleukin-6 (IL-6), nuclear factor kappa-B (NF-κB) and toll-like receptor 4 (TLR4), associated with the TLR4/NF-κB pathway in mice with P. aeruginosa pneumonia. Furthermore, we analyzed the intestinal flora of mice and found that compared with the model group, the abundance and diversity of beneficial bacterial flora of SH treatment groups increased significantly, suggesting that SH can improve the intestinal flora disorder caused by inflammation. In addition, SH improves alpha and beta diversity index and reduces species abundance differences of intestinal flora in pneumonia mice. Discussion Taken together, our presented results indicate that SH may effectively alleviate the acute pulmonary infection induced by P. aeruginosa by reducing the disturbance of regulating immunity and intestinal flora in mice.